Cytokine and Chemokine Profile in Patients with Multiple Myeloma Treated with Bortezomib - Paweł Robak; Edyta Węgłowska; Izabela Dróżdż; Damian Mikulski; Dariusz Jarych; Magdalena Ferlińska; Ewa Wawrzyniak; Małgorzata Misiewicz; Piotr Smolewski; Wojciech Fendler; Janusz Szemraj; Tadeusz Robak (Mediators of Inflammation)
The aim of the study was to determine the levels of selected cytokines and chemokines in the serum of multiple myeloma (MM) patients treated with bortezomib-based regimens. A total of 71 MM patients were examined: 41 with primary refractory disease (17) or early relapse (28), and 30 who were bortezomib sensitive with no progression for at least six months. Patients who demonstrated CR or PR after bortezomib-based therapies longer than six months after treatment discontinuation were designated bortezomib sensitive. Serum cytokine levels were assayed with Bio-Rad Bio-Plex Pro Human Cytokine 27-Plex Assay on the MAGPIX Multiplex Reader and the Bio-Plex® 200 System (Bio-Rad). Higher levels of MIP-1α and lower levels of MIP-1β and IL-9 were associated with better responses to bortezomib-based treatment, and higher levels of IL-1ra and IL-8 were associated with bone involvement. MCP-1 was elevated in patients with hemoglobin<10 g/dl compared to those without anemia. The levels of IL-8, MIP-1α, and TNF-α were significantly higher in patients with renal insufficiency. Only MIP-1α was elevated in patients with hypercalcemia compared to patients with normal calcium levels. In conclusion, distinct cytokines are involved in the pathogenesis of MM and may play a prominent role in the prediction of treatment response. However, a single measurement of serum cytokines should be interpreted with caution and further studies are needed.